Application of queuing models to ship turnaround at the port of Bangkok - Lertvit Tangkosakul; Jones, John Hugh; Chai Muktabhant; Subin Pinkayan (Bangkok : Asian Institute of Technology, 1968)
The purpose of this thesis is to analyze data pertaining to ship turn-around time at the Port of Bangkok from the standpoint of queuing theory and to utilize the findings to draw some inferences regarding application of the theory to certain aspects of the operation of the port at the time of the study. Specifically, ship arrivals and servicing were studied for the period from 1st July 1966 through 30th June 1967. Data were obtained from the records of the Port Authority of Thailand using mark sense cards; the analyses were mostly conducted by sorting the data deck and running this through the IBM-1130 computer which was programmed for the required statistical computations. Two basic elements are necessary for the application of the queuing model to a waiting-line problem: an arrival function and a servicing function. Search for suitable formulations of the distribution of the ship-arrival intervals and the distribution of the duration of berth occupancy were made; selection of suitable distribution functions was made on the basis of the goodness of fit with the observed values. From the arrival and servicing information, and the amounts of delay and thelengths of queues observed at the Port of Bangkok, an evaluation of several queuing models was made. It was concluded that a multiple-channel, negative-exponential arrival, and negative exponential servicing queuing model best suited the conditions observed for berthed ships. None of the models studied gave satisfactory results when applied to the entire system of mooring and berthing spaces.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1968
Keywords: Harbors -- Bangkok; Queuing theory